ANALYSIS OF SCIENCE AND MATHEMATICS DEVELOPMENT OF EARLY CHILDHOOD - Aisyah, Siti; Noorhapizah, Noorhapizah; Hadi, Sutarto (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2018)
Research objectives: 1) Science learning planning in developing math skills of children aged 4-5 years old, 2) Implementing science learning in developing math skills of children aged 4-5 years old, 3) Evaluating science learning in developing the math skills of children aged 4-5 years old. This research used observation method. Results of the research: 1) Planning science learning in developing children math skills, the plan was: teacher prepared daily activities plan, worksheet, material to be delivered, media, assessment sheet and class setting. 2) Learning, the initial activities was teacher and children doing morning gymnastics, the core activity was children were first asked to do math activities related to science such as distinguishing objects that could float and sink in water, 3) Evaluation of science learning implementation in developing children math skills, namely by question and answer method and retelling material method that had been studied. It can be concluded that the real science learning could improve children Math skills.